The effects of dietary compound plant extracts on growth performance, liver and intestine health, and immune related genes expression in hybrid grouper (Epinephelus lanceolatus♂ × Epinephelus fuscoguttatus♀). Issue 119 (December 2021) - Sun, Zhenzhu; Liu, Yang; Wei, Zonglu; Mai, Haobin; Liu, Qingying; Liu, Bo; Zhuang, Yutong; Zou, Danyang; Zhang, Wenqian; Liu, Xinting; Tan, Xiaohong; Ye, Chaoxia
Abstract: The study explored on the effect of dietary compound plant extract supplementation on the growth performance, serum biochemical indicators, liver and intestinal morphological and gene expression levels in the head kidney and spleen of the hybrid grouper ( Epinephelus lanceolatus ♂ × Epinephelus fuscoguttatus ♀). The compound plant extracts (BDG) was a mixture of Bupleurum edulis extract, dandelion extract and Ginkgo biloba extract in a ratio of 1:4:1. Basal diets supplemented with BDG at 0, 0.75, 1.5, 3 and 6 g/kg were fed hybrid grouper for 8 weeks. The results showed that dietary 0.75 and 1.5 g/kg BDG supplementation could significantly increase the WGR and SGR of hybrid grouper ( P  < 0.05). And dietary 0.75 g/kg BDG could also significantly decrease serum aspartate aminotransferase, glucose and lactate dehydrogenase in hybrid grouper ( P  < 0.05). Dietary BGD supplementation protected the integrity of liver and intestinal morphological structure, reduced the accumulation of liver fat. Dietary BDG supplementation might enhance the immunity of hybrid grouper by regulating the expression of antioxidant and inflammation-related genes in head kidney and spleen of hybrid grouper. Our study demonstrated that the growth promoting effect of Bupleurum extract, dandelion extract and Ginkgo biloba extract in the ratio of 1:4:1 as a compound feed additive was better than any of them as a feed additive alone, and the dosage was less. The optimal additive dosage of BDG was 0.75 g/kg in hybrid grouper diets. Highlights: Dietary 0.75g/kg-1.5 g/kg BGD (compound plant extracts) could significantly improve the weight gain rate of hybrid grouper. Dietary BGD supplementation could protect the integrity of liver and reduce the accumulation of liver fat. The optimal additive dosage of BGD was 0.75 g/kg.